Investigation on the microbial profile and waste stabilization during in situ aeration of landfill bioreactors at different temperature - Ng, Wei Hong (2015)
In situ aeration has been a popular and promising method for the advantages it bring about such as reduction of emission of greenhouse gases, accelerating of waste stabilization and settlement, decrease in concentrations of leachate contaminants and being able to provide the optimal conditions for microbial decomposition. The purpose of this study is to investigate and develop a better understanding of the influences of different temperature on the aeration performances and microbial communities. Hence, this give rises to our study using four Landfill Bioreactors (LBRs) NR35 (control), AR35, AR45 and AR55 under anaerobic (35°C), aerobic (35°C), aerobic (45°C) and aerobic (55°C) conditions respectively. The bioreactor operated at 55°C presented a higher mineralization rate compared to 35°C throughout the experimental period, suggesting accelerated biodegradation rates under thermophilic condition. A lag phase in microbial mineralization was observed at 35°C, which was even prolonged at 45°C. In addition, ammonia was significantly stripped out due to aeration. DNA was extracted from leachate sample after one month of bioreactor operation, in order to reveal the microbial variation during the start-up stage. Analysis on the 16s rRNA gene showed that the diversity of the bacterial community was increased after aeration. The Proteobacteria was identified as the most dominant group under the thermophilic temperature. They may exhibit a positive impact on the aerobic bioconversion, as many members of this phylum have diverse metabolic capabilities.